EFFECT OF NONLOCAL ELASTICITY ON INTERNAL-FRICTION PEAKS OBSERVED DURING MARTENSITE-TRANSFORMATION - DOGAN, A (Indian Academy Sciences, 1995)
The internal friction associated with martensite is calculated using elastic interaction energy between dislocations and solute atoms in nonlocal elasticity during low temperature aging process. The relaxation strength depends on the lattice parameter of the crystal as well as the temperature and the heating rate. The peak heights increase with increasing lattice parameter. The proposed model can demonstrate more realistically the shape of the change of internal friction versus temperature when nonlocal elasticity is included.
Keywords: INTERNAL FRICTION; DISLOCATION; SOLUTE ATOMS; SOLID STATE PHASE TRANSFORMATION; MARTENSITE